Therapeutic efficacy of Nigella sativa and Ziziphus lotus: sustainable strategies for diabetes, antimicrobial resistance, and health treatment - Bedir, Alaa S.; Almasri, Razan S.; Al Raish, Seham M. (Frontiers in Nutrition, 2025)
The pharmacological potential of Nigella sativa and Ziziphus lotus, two medicinal plants native to the United Arab Emirates (UAE), is explored in the context of sustainable healthcare strategies. Both plants have demonstrated notable antidiabetic and antimicrobial effects in preclinical studies. For instance, thymoquinone from Nigella sativa has shown glucose-lowering efficacy comparable to metformin in rodent models, while Ziziphus lotus extracts have outperformed acarbose in inhibiting carbohydrate-digesting enzymes. This paper synthesizes findings from ethnobotanical surveys, pharmacological research, and clinical literature to assess their therapeutic relevance. Additionally, it addresses challenges in standardization, sustainable harvesting, and environmental influence on phytochemical composition. While current evidence is promising, gaps remain in clinical validation and regulatory integration. This review aims to inform future research and policy, supporting the incorporation of UAE-native medicinal plants into evidence-based healthcare practices.